Lathyrol inhibits the proliferation of Renca cells by altering expression of TGF-β/Smad pathway components and subsequently affecting the cell cycle - Song, Shengyou; Song, Yalin (Frontiers in Oncology, 2025)
BackgroundRenal cell carcinoma (RCC) is a prevalent type of malignant tumor with high morbidity and mortality. The TGF-β/Smad signaling pathway plays a significant role in the development and progression of RCC.MethodsThis study explored the effects of lathyrol on the proliferation of Renca mouse RCC cells through the inhibition of the TGF-β/Smad signaling pathway and cell cycle arrest. Bioinformatics analysis, cell culture experiments, and animal experiments were conducted to determine the effects of lathyrol on the activity, mRNA expression, and protein expression of RCC cells and RCC xenograft tumors, as well as the expression of cell cycle and cell cycle regulatory proteins.ResultsLathyrol treatment was positively correlated with the inhibitory effect on cell proliferation. The IC values of 786-O cells and Renca cells were comparable. In vitro, lathyrol promoted both protein and mRNA expression of TGF-β1 while increasing Smad6 protein expression and Smad2, Smad3, and Smad4 mRNA expression; concurrently, it suppressed the protein expression of Smad2, Smad3, Smad4, and Smad9. In vivo, lathyrol suppressed the mRNA and protein expression of TGF-β1, TGF-βR1, Smad2, Smad3, Smad4, and Smad9 in RCC xenografts; promoted the protein expression of Smad6; and decreased the protein expression of cyclin D1, cyclin B1, cyclin A1, cyclin E1, CDK6, CDK4, and CDK1 while increasing the expression of P16, P21, and P27.ConclusionLathyrol can repress the expression of key proteins in the TGF-β/Smad signaling pathway, impede signal transduction, arrest the cell cycle progression of Renca cells, and subsequently inhibit the proliferation of RCC cells. Future studies are needed to further explore the mechanism of lathyrol in RCC treatment.